2142. Understanding Errors in Sterile Processing of Surgical Instruments That Lead to Need for Immediate Use Sterilization in the Operating Room. (26th November 2018) - Farrell, John
Abstract: Background: "Flash sterilization", an outdated term for immediate-use sterilization. Immediate use is broadly defined as the shortest possible time between a sterilized item's removal from the sterilizer and its aseptic transfer to the sterile field for use in the procedure for which it was sterilized, but at our institution, immediate-use sterilization of individual unwrapped objects has a very specific definition: this is a vacuum sterilization performed in a pre-vacuum sterilizer (as opposed a gravity displacement steam sterilizer) with a complete cycle composed of a 4-minute exposure time at 275°F followed by a 16 minute dry time. This process was initially intended for a single instrument (e.g., a one of a kind item that may have been dropped during the surgical procedure). Although efforts to minimize flash sterilization at our institution have been successful (we saw only 11 instances in February, 2018), immediate-use sterilization remains common in some operating rooms (OR). Methods: We performed a prospective 30-day study in our sterile processing department (SPD) of the causes of surgical tray errors, which result in need for immediate-use sterilization in the OR. Mistakes were categorized as tray assembly errors, sterilization mistakes, and cart or other errors. Results: Over 30 days, 17, 348 trays were processed in our SPD department for a total of 1, 868 surgical procedures. During this time a total of 86 errors were identified: 38 assembly errors (e.g., 10 trays with missing or incorrect instruments and 10 trays with improper filter placement); 30 sterilization errors (17 documentation errors); 10 case cart mistakes (four missing trays); and eight mistakes categorized as other. Conclusion: We have identified two key opportunities for improvement in tray assembly in our SPD to decrease the need for immediate use sterilization. Recognition of the causes of surgical tray defects can help identify opportunities to decrease errors that result in need for immediate use sterilization. Disclosures: All authors: No reported disclosures.